2020
DOI: 10.1002/nau.24461
|View full text |Cite
|
Sign up to set email alerts
|

Patient demographic and psychosocial characteristics associated with 30‐day recall of self‐reported lower urinary tract symptoms

Abstract: Aims Measurement of self‐reported lower urinary tract symptoms (LUTS) typically uses a recall period, for example, “In the past 30 days….” Compared to averaged daily reports, 30‐day recall is generally unbiased, but recall bias varies by item. We examined the associations between personal characteristics (eg, age, symptom bother) and 30‐day recall of LUTS using items from the Symptoms of Lower Urinary Tract Dysfunction Research Network Comprehensive Assessment of Self‐reported Urinary Symptoms questionnaire. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Gender and age-based demographic variation has previously been detected in the magnitude of the differences between symptom ratings recalled over a period of 1 week or longer and daily ratings. 38,44,45 The sign of the differences at least remained consistent with the broader population. Greater representation of minority groups would enable further investigation of demographic variation in ratings and strengthen future studies.…”
Section: Discussionmentioning
confidence: 58%
“…Gender and age-based demographic variation has previously been detected in the magnitude of the differences between symptom ratings recalled over a period of 1 week or longer and daily ratings. 38,44,45 The sign of the differences at least remained consistent with the broader population. Greater representation of minority groups would enable further investigation of demographic variation in ratings and strengthen future studies.…”
Section: Discussionmentioning
confidence: 58%
“…Using a recall period shorter than the 4 weeks initially assigned to the OES might also be beneficial when a systematic increase or decrease (temporal trends) in symptoms can be expected to occur over 4 weeks, for example, while patients are recovering from an injury or surgery, as was the case for the patients included in the current study. In fact, the presence of variations in symptoms over the course of a recall period, 5 , 11 , 41 in particular temporal trends, 40 has been found to threaten the accuracy of rating symptoms by recall. It appears reasonable that longer recall periods might be more vulnerable to these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of orthopedic surgery, other medical fields have also investigated the effects of patient recall bias on reported outcomes. For example, Flynn et al assessed 30-day patient-reported recall of urinary tract infection symptoms in 254 patients [ 32 ]. They found that recall bias significantly affected answers on nine items that were tested, among 25% of the study population.…”
Section: Reviewmentioning
confidence: 99%